Acute exacerbations of fibrotic interstitial lung diseases. Issue 5 (19th August 2019) - Suzuki, Atsushi; Kondoh, Yasuhiro; Brown, Kevin K.; Johkoh, Takeshi; Kataoka, Kensuke; Fukuoka, Junya; Kimura, Tomoki; Matsuda, Toshiaki; Yokoyama, Toshiki; Fukihara, Jun; Ando, Masahiko; Tanaka, Tomonori; et al.
ABSTRACT: Background and objective: Acute exacerbation (AE) is a severe complication of idiopathic pulmonary fibrosis (AE‐IPF). In 2016, an international working group revised its definition and diagnostic criteria; however, few studies have assessed the frequency and prognosis of AE in patients with other fibrotic interstitial lung diseases (FILD). Methods: We used data from 1019 consecutive interstitial lung disease (ILD) patients initially evaluated between January 2008 and July 2015. All subject diagnoses were made by multidisciplinary discussion in December 2018. ILD was categorized as IPF ( n = 462) and other FILD which included non‐specific interstitial pneumonia ( n = 22), chronic hypersensitivity pneumonitis ( n = 29), connective tissue disease‐associated ILD ( n = 205) and unclassifiable ILD ( n = 209). Using the 2016 definition of AE‐IPF, we identified all subjects with an AE. Results: During the observational period, 193 patients experienced a first AE (AE‐FILD n = 69, AE‐IPF n = 124). The time to first AE was significantly longer in FILD than IPF (log‐rank test, P < 0.001). After adjusting for potentially influential confounders, FILD remained a significant predictor of longer time to first AE compared with IPF (hazard ratio: 0.453; 95% CI: 0.317–0.647, P = 0.006). In a multivariate Cox proportional analysis, baseline disease severity was closely associated with the incidence of AE‐ILD. Even after adjustment for other clinical variables, AE had a negative impact on overall survival. AE‐FILD and AE‐IPF showed similar poor short‐term outcomes. Conclusion: All forms of ILD are at risk of AE and have a similar outcome to AE‐IPF. Abstract : This study reveals that all forms of fibrotic interstitial lung diseases (FILD) are at risk of acute exacerbations (AE) and have similar outcomes to AE of idiopathic pulmonary fibrosis (AE‐IPF). Clinicians are recommended to consider all forms of FILD to be at risk of AE.